Innovative Management for Asian Futures A Comparative Study of Cultural Industries in Thailand and Korea (Part 2 – Thailand) - Disatapundhu, Suppakorn (Journal of Urban Culture Research, 2014)
In the recent years, following the boom of the cultural policies at the international level, Thailand has turned to place its emphasize on the idea of “cultural and creative industries” at the academic and policy-making level especially in its art and design institutions. Academic disciplines in arts management, information and technology, communication arts, media studies, and economics are developing into the world where they can be blended together into multiple levels of knowledge management. The policy development, and implementation plans are embracing these industries into its national platforms, integrating the culture and economics together. Therefore, this two-part article aims to illustrate a comparative study of the cultural industries in Thailand and Korea at the level of their operational models and policies. It will demonstrate certain economic values and potential creative industries in Thailand as well as propose recommendations for their development and enhancement.